Design e complexidade: em busca de um novo ethos projetual - Bittencourt, Paulo Henrique da Rocha (Universidade do Vale do Rio dos Sinos, 2021)
The thesis proposes the conception of a design method and its theories, in the light of complexity theory, capable of integrating order and disorder, opening and closing, certainties and uncertainties, regularities and randomness, continuity and rupture, nature and culture to their processes, reason and imagination. Therefore, it presents principles for the regeneration of design action towards the renewal of the design ethos, aimed at creativity, diversity, dialogue, fraternity, overcoming technoculture, reconnecting dispersed knowledge and experiences and, finally, design of new possibilities of living the world in society. The work is organized in four movements that narrate the theoretical-methodological path of the research carried out in the dialogue with design experiences. It starts from the discussion about the proximity of design to the notion of form and presents the idea of a form-in-transformation, which establishes its own system for each project and is established by it, according to processualities founded on the order-disorder-organization-interaction. It then suggests the concept of design as the process of designing an original form that institutes a new unit organized from the cut of matter by substance. In this case, the project would be the formal expression of the design in its entirety. The First Movement takes up the concept of a complex system, understood as a whole that transforms itself at the same time that its parts are transformed, based on the relationships engendered between them, new emergencies, entrances and exits enabled by its organizational opening. The Second Movement points to the concept of time in design as chrono-cairo, that is, a time-nottime, which acts continuously and discontinuously on everything that exists, just as it precedes phenomenal existence by appearing in a timely manner. in crises and bifurcations. It also associates the idea of event as everything that happens in chronocairo and that impacts the system. Event, in turn, is the instance that allows events to occur, intra and ecosystemically. The Third Movement discusses the ecosystem nature of subjectivation processes, with the recognition of individuals as bio-anthropo-social subjects and the simultaneous movement of closing the “I” to the “other” (selfishness) and opening the “I” for the “other” (altruism). Projecting devices are a web of projective dispositions aimed at the subject to project himself, in “himself” and in the “other”, for the formation of a “we”. Finally, the Fourth Movement advances in understanding the concept of crisis and how a situation of systemic destabilization can be used (or designed) to promote transformations. In this sense, it proposes the idea of crisis: the conception of projecting devices that generate events capable of causing deviations and/or ruptures in the regulation devices and, consequently, fluctuations, bifurcations, retroactions, emergencies, novelty and transformation in design processes.
Keywords: Design; Forma; Acontecimento; Tempo; Ecossistema; Sujeito; Dispositivo; Complexidade; Form; Event; Time; Ecosystem; Subject; Dispositif; Complexity; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial